Generation of human induced pluripotent stem cell-derived cerebral organoids for cellular and molecular characterization - Corina Anastasaki; Anna F. Wilson; Alexander S. Chen; Michelle L. Wegscheid; David H. Gutmann (STAR Protocols, 2022)
Summary: Human induced pluripotent stem cell (hiPSC)-derived cerebral organoids (COs) can serve as an in vitro model for studying normal and pathologic human brain development. Here, we optimized existing protocols to streamline the generation of forebrain COs from hiPSCs. We employ these COs to define the impact of disease-causing mutations on cell fate, differentiation, maturation, and morphology relevant to neurodevelopmental disorders. Although limited to forebrain CO identity, this schema requires minimal external interference and is amenable to low-throughput biochemical assays.For complete details on the use and execution of this profile, please refer to Anastasaki et al. (2020) and Wegscheid et al. (2021).